Mengukur kinerja keuangan pada UKM akibat pandemi Covid-19 - Bertha Silvia Sutejo; Marwin Antonius Rejeki Silalahi (Universitas Kristen Maranatha, 2021)
Competition is increasing from time to time between SMEs (Small and Medium-Sized Enterprieses), for this reason, this research was conducted by measuring SMEs' financial performance in Surabaya due to the impact of the Covid-19 virus. There are four variables analyzed, namely innovative, risk-taking, proactiveness, and competitive aggressiveness. The weaknesses of SMEs are generally in terms of managerial abilities, capital, and human resources. Apart from this, aspects outside the company are one of the causes of SMEs' reduced performance in Indonesia. This study aims to strengthen the results of previous research. The results of this study are used to help the community, especially investors and academics, to understand the importance of entrepreneurship in improving the financial performance of SMEs during the Covid-19 pandemic. This research scale was adopted from existing literature. The research data used secondary data. The research method used was purposive sampling. This study uses reliability and validity tests to measure the scale, classic assumption tests to assess the feasibility of data, and hypothesis testing using multiple regression tests. The results of this study found that innovation, risk-taking, and proactiveness affect financial performance, while competitive aggressiveness does not affect financial performance.